From attention to memory along the dorsal-ventral axis of the medial prefrontal cortex: some methodological considerations - Cassaday, Helen J.; Nelson, Andrew J. D.; Pezze, Marie A. (Frontiers in Systems Neuroscience, 2014)
Distinctions along the dorsal-ventral axis of medial prefrontal cortex (mPFC), between anterior cingulate (AC), prelimbic (PL) and infralimbic (IL) sub-regions, have been proposed on a variety of neuroanatomical and neurophysiological grounds. Conventional lesion approaches (as well as some electrophysiological studies) have shown that these distinctions relate to function in that a number behavioural dissociations have been demonstrated, particularly using rodent models of attention, learning and memory. For example, there is evidence to suggest that AC has a relatively greater role in attention, whereas IL is more involved in executive function. However, the well-established methods of behavioral neuroscience have the limitation that neuromodulation is not addressed. The neurotoxin 6-hydroxydopamine has been used to deplete dopamine (DA) in mPFC sub-regions, but these lesions are not selective anatomically and noradrenalin is typically also depleted. Microinfusion of drugs through indwelling cannulae provides an alternative approach, to address the role of neuromodulation and moreover that of specific receptor subtypes within mPFC sub-regions, but the effects of such treatments cannot be assumed to be anatomically restricted either. New methodological approaches to the functional delineation of the role of mPFC in attention, learning and memory will also be considered. Taken in isolation, the conventional lesion methods which have been a first line of approach may suggest that a particular mPFC sub-region is not necessary for a particular aspect of function. However, this does not exclude a neuromodulatory role and more neuropsychopharmacological approaches are needed to explain some of the apparent inconsistencies in the results.